Digital Innovation Management for Sustainable Development – A Model Approach - Renata Szanter; Katarzyna Łobacz (Journal of Modern Science)
The article examines the digitalisation of business innovation processes with a focus on their potential to positively contribute to achieving sustainable development goals. A model-based approach is employed, presenting analytical and measurement frameworks that connect the organisation and digitalisation of innovation processes with the elements and conditions of sustainable development. The analysis provided valuable insights into the dynamics and trajectories of innovation processes supported by digital tools. It was established that prioritising sustainability within innovation activities is feasible even without the adoption of digital tools, provided that appropriate procedures, evaluation criteria, and involvement in ideation and decision-making processes are in place. However, the integration of digital tools and platforms into the development and implementation of innovations can significantly enhance the alignment of activities with sustainability goals, leading to more sustainable outcomes across all three dimensions of sustainable development. The operationalisation of the innovation process outlined in this study offers a practical guide for managers, demonstrating how to standardise innovation management within businesses, identify which elements of the process can be digitalised, and leverage digital tools to apply and monitor sustainability considerations at various stages of developing and implementing new solutions. The proposed model also provides a means to measure the extent and intensity of digitalisation in innovation practices and their focus on advancing sustainable development goals.